Augmented Reality Game for Anti Corruption Education in Behavior of Students of University - pieter santoso hadi; Albertus Dwiyoga Widiantoro; Hendra Prasetya (Soegijapranata Catholic University, 2019)
The behavior of students of university in their study have an effect in their character toward corruption. As motivation effects the behavior and the behavior effects the character of person [1]. Game is one of interactive digital media that can be used as educational tools. Game education is a digital game which structured for educational purpose [2]. Augmented Reality game is a live direct or indirect view from real word perspective whose elements are augmented by computer-generated in which a view of reality is modified even diminished by a computer [3]. This Journal contains the result of using Augmented Reality game as education media for anti corruption education in behavior of university students. Education materials consist of bad behavior of university students that appear on their study and their relation with corruption.Keywords – Augmented Reality, Game, Behavior, University, Student, Education